Midwifery Complementary Treatment with The Application of Oxytocin Massage Using Lavender Aromatherapy Oil on Breast Milk Production in Postpartum Mothers - Ni Made Rai Widiastuti; Ketut Novia Arini; Maria Gabriela Yuniati (Babali Health, 2022)
Introduction: One of the non-pharmacological methods used to increase breast milk production is known as complementary care, one of which is by giving oxytocin massage using lavender aromatherapy oil. The purpose of this study was to determine the effect of oxytocin massage using lavender aromatherapy oil on postpartum mother's milk production. Methods: This study used a quasi-experimental with pre-test and post-test with a control group. The sample in this study were postpartum mothers with a sample size of 15 respondents in the treatment group and 15 respondents in the control group who met the criteria. The intervention group received oxytocin massage services with lavender aromatherapy oil starting on the 2nd day postpartum, while the control group received breastfeeding assistance, then on the 6th day both groups measured milk production using a Brust Pump. The instrument used is the observation sheet. Hypothesis testing was carried out using the Mann-Whitney test. Results: Based on the calculation of the Mann-Whitney test, the sig value (p value) is 0.000, where p value <0.05, which means that oxytocin massage using lavender aromatherapy oil has a significant effect on maternal milk production in normal postpartum. Conclusion: Combination complementary therapy between oxytocin massage and lavender aromatherapy can increase breast milk production in postpartum mothers in Denpasar City.